2022
DOI: 10.1101/2022.11.16.22282100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Particulate matter air pollution and COVID-19 infection, severity, and mortality: A systematic review

Abstract: Background and objective Ecological studies indicate ambient particulate matter ≤2.5mm (PM2.5) air pollution is associated with poorer COVID-19 outcomes. However, these studies cannot account for individual heterogeneity and often have imprecise estimates of PM2.5 exposure. We review evidence from studies using individual-level data to determine whether PM2.5 increases risk of COVID-19 infection, severe disease, and death. Methods Systematic review of case-control and cohort studies, searching Medline, Embase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…An increase of 10.5 ± 2.5 % in COVID-19 mortality per 1 μg/m 3 increase of PM2.5 concentration was observed in this study [ 9 ]. Similar findings were observed in a meta-analysis of 18 studies, which revealed that an increase in PM2.5 concentration led to a significant increase (OR = 2.27 per 10 μg/m³ change, 95% CI 1.41–3.66) in COVID-19 hospitalizations or critically ill patients [ 26 ]. The findings of our study are consistent with previous research indicating an elevated risk of hospitalization and/or mortality in COVID-19 patients linked to exposure to increased PM2.5 concentration.…”
Section: Discussionsupporting
confidence: 85%
“…An increase of 10.5 ± 2.5 % in COVID-19 mortality per 1 μg/m 3 increase of PM2.5 concentration was observed in this study [ 9 ]. Similar findings were observed in a meta-analysis of 18 studies, which revealed that an increase in PM2.5 concentration led to a significant increase (OR = 2.27 per 10 μg/m³ change, 95% CI 1.41–3.66) in COVID-19 hospitalizations or critically ill patients [ 26 ]. The findings of our study are consistent with previous research indicating an elevated risk of hospitalization and/or mortality in COVID-19 patients linked to exposure to increased PM2.5 concentration.…”
Section: Discussionsupporting
confidence: 85%